An unusual case of osmotic demyelination syndrome without electrolyte changes in a patient with diabetes - Kote, Shrikant S.; Khandelwal, Ankur; Pathak, Deba G.; Nath, Rupankar (Journal of Neuroanaesthesiology and Critical Care, 2016)
Central pontine myelinolysis (CPM) is a demyelinating disease of the pons which is also associated with the demyelination of extrapontine areas of the central nervous system. Although the aetiology and pathogenesis are unclear, CPM is usually associated with hyponatremia or its rapid correction. Malnutrition and chronic alcoholism are also the common underlying conditions. Herein, we report a rare presentation of ODS, secondary to hyperosmolar hyperglycaemic state. We observed a 37-year-old female with diabetes type 1 and hypertension who presented with ataxia, dysarthria and pseudobulbar effect which evolved over a duration of few weeks at home with no evidence of hyponatremia or its rapid correction and no history of alcohol abuse or malnutrition.
Keywords: Central pontine myelinolysis; diabetes mellitus; extrapontine myelinolysis; hyperosmolar hyperglycaemic state; osmotic demyelination syndrome